2020
DOI: 10.1103/physrevd.101.024039
|View full text |Cite
|
Sign up to set email alerts
|

Eclipses of continuous gravitational waves as a probe of stellar structure

Abstract: Although gravitational waves only interact weakly with matter, their propagation is affected by a gravitational potential. If a gravitational wave source is eclipsed by a star, measuring these perturbations provides a way to directly measure the distribution of mass throughout the stellar interior. We compute the expected Shapiro time delay, amplification and deflection during an eclipse, and show how this can be used to infer the mass distribution of the eclipsing body. We identify continuous gravitational wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 99 publications
0
15
0
Order By: Relevance
“…The same physics was exploited to probe diffuse NFW dark matter profile with GWs [11]. Other ways to measure the lens mass profile include the well-known weak lensing by a galaxy and the eclipse by a lens star [27].…”
Section: Solar Diffractionmentioning
confidence: 99%
“…The same physics was exploited to probe diffuse NFW dark matter profile with GWs [11]. Other ways to measure the lens mass profile include the well-known weak lensing by a galaxy and the eclipse by a lens star [27].…”
Section: Solar Diffractionmentioning
confidence: 99%
“…In this respect, Liao et al (2019) have demonstrated that diffraction and interference effects may, albeit rarely, show up in continuous GW signals, and that the amplitude and phase modulations arising due to lensing can non-negligibly affect parameter estimation (see also de Paolis et al 2001;Diego et al 2019;Marchant et al 2020;Meena & Bagla 2020;Mishra et al 2021). However, these authors concentrated on the case of a single point-mass lens, where a closed-form expression for the lensing flux is available (Nakamura & Deguchi 1999), thereby allowing for analytically tractable computations.…”
Section: Introductionmentioning
confidence: 99%
“…A number of possibilities to identify a lensed GW signal have been proposed. One can look for signatures of multiple images or microlensing within GW data [23,29,[36][37][38][39][40]. Alternatively, one could search for a population of apparently high-mass binary events produced by lensing magnification [19,26,41].…”
Section: Introductionmentioning
confidence: 99%